SKENARIO PENGEMBANGAN EKOWISATA SEBAGAI UPAYA MEMPERTAHANKAN HUTAN LINDUNG WOSI RENDANI DI KABUPATEN MANOKWARI SCENARIOS OF ECOTOURISM DEVELOPMENT AS EFFORT IN MAINTAINING IN PROTECTED FOREST WOSI RENDANI IN MANOKWARY REGENCY - Mahmud Mahmud; Mutakim Mutakim; Wahyudi Wahyudi (Balai Penelitian Dan Pengembangan Teknologi Hasil Hutan Bukan Kayu, 2022)
Currently, protected forest are in the spotlight regarding national food security that can be applied other than in production forest. This study aims a study ecotourism scenarios development in the Protected Forest of Wosi Rendani (PFWR). Research using techniques for observation, interviews and case studies with a mix method approach. Meanwhile, data analysis using a community based ecotourism development based on the potential and threat level. The results showed potential such as flora, abundant water, caves and waterfalls. Meanwhile, the threat is rather steep slopes with soil characteristics that are not suitable for seasonal farming. The community has a dominant positive and accepting perception and attitude towards the development of ecotourism. Scenarios ecotourism development in PFWR in order to keep functioning as a protected forest, such as: fruit tourism villages, limited cave tourism, communal water reservoirs and limited waterfall tourism. By making a fruit tourism village, the fallow land becomes more productive because it is planted with fruit trees, so that in the future Manokwari becomes a fruit food estate originating from PFWR. Through limited caves tourism and waterfalls, it is hoped that local people's unemployment will decrease, income will increase so that they are able to meet their daily needs properly. The availability of abundant water by making reservoirs means that the community around PFWR maintains, protects and maintains the conservation of protected forests, because there is a reciprocal relationship if protect the forest, there will be water available.